Illness Perception of Patients with Functional Gastrointestinal Disorders - Xiong, Na-na; Wei, Jing; Ke, Mei-yun; Hong, Xia; Li, Tao; Zhu, Li-ming; Sha, Yue; Jiang, Jing; Fischer, Felix (Frontiers in Psychiatry, 2018)
Objective: To investigate the illness perception characteristics of Chinese patients with functional gastrointestinal disorders (FGID), and the mediating role between symptoms, psychopathology and clinical outcomes. Methods: Six illness groups from four outpatient departments of a general hospital in China were recruited, including the FGID patient group. The modified and validated Chinese version of the illness perception questionnaire-revised was utilized, which contained three sections: symptom identity, illness representation and causes. The 12-item short-form health survey was utilized to reflect the physical and mental health related quality of life (HRQoL). The Toronto alexithymia scale was used to measure the severity of alexithymia. Additional behavioral outcome about the frequency of doctor visits in the past 12 months was measured. Pathway analyses with multiple-group comparisons were conducted to test the mediating role of illness perception. Results: Overall, 600 patients were recruited. The illness perceptions of FGID patients were characterized as with broad non-gastrointestinal symptoms (6.8±4.2), a negative illness representation (more chronic course, worse consequences, lower personal and treatment control, lower illness coherence, and heavier emotional distress), and high numbers of psychological and culture-specific attributions. Fit indices of the three hypothesized path models (for physical and mental HRQoL and doctor-visit frequency, respectively) supported the mediating role of illness perceptions. For example, the severity of alexithymia and non-gastrointestinal symptoms had significant negative effect on mental quality of life through both direct (standardized effect: -.085 and -.233) and indirect (standardized effect: -.045 and -.231) influence via subscales of consequences, emotional representation, and psychological and risk factor attributions. Multi-group confirmatory factor analysis showed similar psychometric properties for FGID patients and the other disease group. Conclusions: The management of FGID patients should take into consideration dysfunctional illness perceptions, non-gastrointestinal symptoms and emotion regulation.